Cytomorphology and Clinicopathologic Correlation of the Recurrent and Metastatic Adult Granulosa Cell Tumor of the Ovary: A Retrospective Review. Issue 12 (5th August 2016) - Harbhajanka, Aparna; Bitterman, Pincas; Reddy, Vijaya B.; Park, Ji‐Weon; Gattuso, Paolo
Abstract : Granulosa cell tumors (GCT) of the ovary are low grade tumor with a potential ability of late pelvic recurrences and distant metastases. However, there is sparse literature on the cytopathologic features of metastatic granulosa cell tumors (MGCT). Between 2000 and 2014, eight cases of MGCT were diagnosed by FNA. Clinical, cytologic, and histopathologic features were reviewed. The age ranged from 34 to 84 years. Metastases were found in abdominal wall (4 cases), pelvic mass (1 case), liver (2 cases), and lung (1 case). The time to metastasis ranged from 1 to 14 years. All cases were hypercellular, with both large and small overlapping cell clusters and individual cells. The cytologic features included: naked nuclei (8/8 cases), Call‐Exner bodies (2/8 cases), and prominent metachromatic stroma (3/8 cases). Moderate cytoplasm (4/8 cases) to scant delicate cytoplasm (4/8 cases) was seen. Cytoplasmic vacuoles were also noted (6/8 cases). N/C ratios were high although lower than small round cell tumors like lymphoma. Prominent, central nucleoli were also present (6/8 cases) as well as nuclear grooves (2/8 cases). Cell block was available in 3/8 cases and all were positive for inhibin immunostain. Histologic examination of the metastatic tissue confirmed MGCT. The important cytologic features of GCT like uniformity of tumor cells, nuclear grooves and Call‐Exner bodies are occasionally present in MGCT. Prominent nucleoli and many naked nuclei were frequent. Therefore, the accurate interpretation of cytologic findings of MGCT requires cytohistologic correlation and inhibin positivity to avoid unnecessary surgical interventions for diagnostic purposes. The possibility of late recurrence of GCT should be kept in mind. Diagn. Cytopathol. 2016;44:1058–1063. © 2016 Wiley Periodicals, Inc.